HOW RESTAURANT ENTERPRISES MANAGE LOYALTY OF GUESTS IN EFFECTIVE WAYS - Yokubov Murodjon Ruslanovich (Journal of new century innovations, 2023)
Abstract: The research paper demonstrates the how to keep guests loyal in the restaurant, as a set of measures aimed at creating a guest experience in restaurant by providing individual and exclusive offers